2019
DOI: 10.3390/nano9030351
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Methane Sensing Properties of WO3 Nanosheets with Dominant Exposed (200) Facet via Loading of SnO2 Nanoparticles

Abstract: Methane detection is extremely difficult, especially at low temperatures, due to its high chemical stability. Here, WO3 nanosheets loaded with SnO2 nanoparticles with a particle size of about 2 nm were prepared by simple impregnation and subsequent calcination using SnO2 and WO3·H2O as precursors. The response of SnO2-loaded WO3 nanosheet composites to methane is about 1.4 times higher than that of pure WO3 at the low optimum operating temperature (90 °C). Satisfying repeatability and long-term stability are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 59 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…It also has advantages of low cost, high chemical stability, and excellent process-dependent reproducibility. Recent progress has shown that WO 3 with various morphologies is promising in applications of gas sensors to detect toxic gases [8,9,10]. Moreover, WO 3 crystals can be synthesized through various physical and chemical methods and the crystalline quality and morphology can be easy controlled through varying the process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It also has advantages of low cost, high chemical stability, and excellent process-dependent reproducibility. Recent progress has shown that WO 3 with various morphologies is promising in applications of gas sensors to detect toxic gases [8,9,10]. Moreover, WO 3 crystals can be synthesized through various physical and chemical methods and the crystalline quality and morphology can be easy controlled through varying the process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous applications, WO 3 with various morphologies has received extensive attention as a forward-looking gas-sensing material due to its high sensitivity and stability toward target gases [1,5]. For example, it has been used to detect methane vapor, NO 2 gas, and CO gas with distinct sensing responses [1,6]. However, WO 3 has various crystallographic structures [2].…”
Section: Introductionmentioning
confidence: 99%
“…WO 3 nanosheets loaded with SnO 2 nanoparticles exhibit enhanced methane-sensing performance. Moreover, it has been shown that the loading content of SnO 2 nanoparticles has an important influence on the sensing behavior of WO 3 –SnO 2 nanocomposites [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SnO 2 -loaded WO 3 nanosheets showed 1.4 times higher response towards CH 4 than pure WO 3 at working temperature of 90°C. The highly reactive sites as a result of defect formation at the SnO 2 -loaded WO 3 heterojunction, and oxygen chemisorptions at the dangling bonds of W atoms of WO 3 nanosheets result in significant enhancement in the sensing behaviour [ 166 ]. The V 2 O 5 nanostructures-based sensor showed a response of about 6.52–8% at 150°C towards 50–500 ppm CH 4 concentration and exhibited its specificity towards the C–H bond (CH 4 ) [ 174 , 177 ].…”
Section: Greenhosue Gas Sensorsmentioning
confidence: 99%